2016
DOI: 10.1016/j.lindif.2016.09.016
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social capital on self-efficacy and study success among first-year university students

Abstract: University programmes increasingly implement small-group teaching, with the assumption that students' social capital fosters academic achievement. However, few studies address the impact of social capital on the study success of first-year students. The current study addresses this research gap, examining the extent to which social capital relates to study success for first-year university students and whether this effect differs for high-, average-, and low-achieving high school students. Survey data collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 74 publications
9
60
0
5
Order By: Relevance
“…Lower-achieving students do not connect with advanced peers and have fewer connections that might be useful to improve their achievement. These results are consistent with our recent findings that high achievers benefit more from their friends for study success than low achievers (Brouwer et al 2016b). What makes lower achievers connect less with others when these connections would be quite useful?…”
Section: Discussionsupporting
confidence: 92%
“…Lower-achieving students do not connect with advanced peers and have fewer connections that might be useful to improve their achievement. These results are consistent with our recent findings that high achievers benefit more from their friends for study success than low achievers (Brouwer et al 2016b). What makes lower achievers connect less with others when these connections would be quite useful?…”
Section: Discussionsupporting
confidence: 92%
“…This emphasizes the role of a student's context and personality traits in determining their experience. A 2016 study by Brouwer, Jansen, Flache, & Hofman (2016) indicated that two categories of social capital-peer capital (help seeking, collaboration, and fellow students' support) and faculty capital (mentor support)-contribute positively to study success among first year students. Self-efficacy, in particular, has been shown to be a predictor of academic success and may be a student characteristic through which the effects of social capital are mediated, as students enter university with beliefs about their ability to succeed (Bandura, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…The learning community structure establishes an interactive, collaborative environment that helps students' transition to the university setting, by encouraging social interaction and building social capital (Brouwer, Jansen, Flache, & Hofman, 2016). Social capital can be defined as a person's access to and use of valuable resources (e.g., information, knowledge), obtained through social relations or networks, based on trust, social norms, and values that help him or her attain personal goals (Coleman, 1990;Lin, 1999;Putnam, 1995).…”
Section: Social Capital In Lcsmentioning
confidence: 99%